Epstein−Barr virus reactivation induces MYC‐IGH spatial proximity and t(8;14) in B cells. Issue 3 (13th March 2023) - Sall, Fatimata Bintou; Shmakova, Anna; Karpukhina, Anna; Tsfasman, Tatyana; Lomov, Nikolai; Canoy, Reynand Jay; Boutboul, David; Oksenhendler, Eric; Toure, Awa Oumar; Lipinski, Marc; Wiels, Joëlle; Germini, Diego; et al.
Abstract: Burkitt lymphoma (BL) is a B cell malignancy associated with the Epstein−Barr virus (EBV). Most BL cases are characterized by a t(8;14) chromosomal translocation involving the MYC oncogene and the immunoglobulin heavy chain gene ( IGH ). The role of EBV in promoting this translocation remains largely unknown. Here we provide the experimental evidence that EBV reactivation from latency leads to an increase in the proximity between the MYC and IGH loci, otherwise located far away in the nuclear space both in B‐lymphoblastoid cell lines and in patients' B‐cells. Specific DNA damage within the MYC locus, followed by the MRE11‐dependent DNA repair plays a role in this process. Using a CRISPR/Cas9‐based B cell model to induce specific DNA double strand breaks in MYC and IGH loci, we have shown that the MYC‐IGH proximity induced by EBV reactivation leads to an increased t(8;14) translocation frequency. Statement of significance: This study analyzed the role of Epstein−Barr virus (EBV) reactivation in the occurrence of Burkitt lymphoma‐specific t(8;14) chromosomal translocations. Our findings demonstrate that EBV reactivation induces MRE11‐dependent proximity between the MYC and IGH loci in B cells, which translates into elevated t(8;14) rates upon induction of DSBs within these loci.